The seasonal climate of the Early-Middle Jurassic, Cleveland Basin, England - Morgans, H; Hesselbo, S; Spicer, R (1999)
Diverse aspects of the fossil floras of the Early to Middle Jurassic (Cleveland Ironstone and Dogger Formations and Ravenscar Group; Pliensbachian-Bathonian stages) of North Yorkshire, England, have been investigated in order to better define the prevailing Early-Middle Jurassic paleoclimate. Growth rings in fossil woods have been characterized in terms of their 'mean sensitivity'; overall woods are 'complacent' and grew well within the bounds of their climatic tolerance, but woods from the oldest and, particularly, youngest parts of the succession analyzed (the Dogger and Scalby Formations, respectively) show greater interseasonal variation in growth. Intraseasonal variability in growth is indicated by the ubiquitous presence of false rings. Further evidence of seasonality from the fossil floras is the occurrence of leaf beds (ginkgophytes and Nilssoniopteris) interpreted as resulting from the deposition of leaves shed from deciduous plants during flood seasons. Charcoal is ubiquitous throughout the succession and wood samples often show 'checking' of cell walls as a microscopic feature. These observations, combined with a consideration of the depositional and diagenetic history of the host sedimentary rocks, indicate the predominance of a winter-wet seasonal paleoclimate, which was characterized by greater aridity in the late Bajocian-Bathonian relative to the Pliensbachianmid Bajocian. The increasing aridity towards the close of this interval may have been partly a function of regional withdrawal of the extensive seaway that characterized the area for most of the preceding Early Jurassic, but also may have been an early manifestation of the continent-wide arid phase that affected Eurasia during the Late Jurassic.